Tindak Tutur dalam Pojok Mang Usil di Surat Kabar Harian Kompas - Amazeli, Renzy Agathy; Agustina, Agustina; Ngusman, Ngusman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study were (1) to describe the speech act genre in the coloumn containing phity rubric of Mang Usil in the Kompas Daily, (2) the speech act strategy in the coloumn containing phity rubric of Mang Usil in the Kompas Daily, and (3) the speech act function in the coloumn containing phity rubric of Mang Usil in the Kompas Daily. The data of this study were the 76 pairs of the testimony and statement sentences in the coloumn containing phity rubric of Mang Usil in the Kompas Daily September 2012. The data resources of this study was the coloumn containing phity rubric of Mang Usil in the Kompas Daily September 2012. The data was collected by using the data technic analisys. The result of this study were the speech act genre that the most showed is the representatif speech act, the speech act strategy that the most showed was the disguised of speech act, and the speech act function that the most showed were collaborative and conflictive.